FGF23: A Review of Its Role in Mineral Metabolism and Renal and Cardiovascular Disease - Kurpas, Anna (Dis Markers, 2021)
FGF23 is a hormone secreted mainly by osteocytes and osteoblasts in bone. Its pivotal role concerns the maintenance of mineral ion homeostasis. It has been confirmed that phosphate and vitamin D metabolisms are related to the effect of FGF23 and its excess or deficiency leads to various hereditary diseases. Multiple studies have shown that FGF23 level increases in the very early stages of chronic kidney disease (CKD), and its concentration may also be highly associated with cardiac complications. The present review is limited to some of the most important aspects of calcium and phosphate metabolism. It discusses the role of FGF23, which is considered an early and sensitive marker for CKD-related bone disease but also as a novel and potent cardiovascular risk factor. Furthermore, this review gives particular attention to the reliability of FGF23 measurement and various confounding factors that may impact on the clinical utility of FGF23. Finally, this review elaborates on the clinical usefulness of FGF23 and evaluates whether FGF23 may be considered a therapeutic target.